PENGARUH MINAT BACA DAN KEAKTIFAN BELAJAR SISWA TERHADAP PRESTASI BELAJAR MATA PELAJARAN KORESPONDENSI - Marta Kusuma Rahmawanto (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2019)
The purpose of this study is to determine: (1) the significant impact of reading interest with the learning achievement on the subjects of correspondence; (2) the significant impact of students participation with the learning achievement on the subjects of correspondence; (3) the significant impact of reading interest and students participation with the learning achievement on the subjects of correspondence. This research is a type of quantitative research using a correlational approach. The population in this research were all students of class X Automation and Office Administration at Vocational High School Batik 1 Surakarta which amounted to 83 students. The sampling technique used is total sampling. Technique of collecting data used was questionnaire and documentation. The data analysis techniques using multiple linier regression analysis. The results of the research showed: (1) there is significant impact between reading interest with the learning achievement on correspondence. It can be shown by the statistical t test of (2,421 > 1,99); (2) there is significant impact between students participation with the learning achievement on. It can be shown by the statistical t test of (3,958 > 1,99); (3) there is significant impact between reading interest and students participation with the learning achievement on correspondence. It can be shown by the statistical F test of (40,416 > 3,11). the results of this research indicate an effective contribution together by 50.3% and the remaining 49.7% is impact by other variables not included in this research.